On the approximation of a bounded solution of a linear differential equation in a Banach space - Gorodnii, M. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the problem of approximation of a bounded solution of a linear differential equation by solutions of the corresponding difference equations in a Banach space.